Sparsa collecta. the collected essays of W.C. van Unnik - Unnik, W. C. van 1910-1978. (Novum Testamentum, Supplements, 2014)
Between 1973 and 1983 three volumes of collected essays by Willem C. van Unnik appeared under the title Sparsa Collecta . All the essays in these volumes had been published between 1930 and 1970. The editors of the present volume decided to publish a fourth volume with a selection of his later papers, some of which appear here for the first time in English (they were originally published in Dutch).